(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
In robotic navigation, wheels are highly efficient for engineered surfaces. However, they need to be more efficient when navigating over rough terrains. Evolution has resulted in limbed creatures that are highly adapted to extreme terrains. This paper explores the design of robotic legs for sagittal motion in uneven terrains. The paper builds upon locomotion theories to identify geometrical features of the leg and groups of legs as a function of terrain features. The predictions of the analytical models are compared against observations in the animal kingdom. The study is focused on legs that can be represented with two degrees of freedom, connected via revolute joints. It uses simplified terrain features and reduced-order dynamic models to evaluate the cost of transport associated with the different legs and terrain configurations. Examples of animal and animal-inspired robots to which the model applies include crabs, horses, and some insects. The model is expected to help design more agile robots and be extensible to designing human prostheses and end effectors for robotic manipulators.